Pengembangan alat uji tarik dengan beban maksimal 2 kN - Zariatin, D.L.; Kurniawan, R.M.; Ikhsan, N. (Universitas Mataram, 2021)
To find out the characteristics of a material, various tests are needed. One of them is the tensile test. Various brands of tensile testing machines for natural fibers and composite materials applications are available on the market. However, it becomes a challenge to design and manufacture a prototype tensile test machine by utilizing existing components. The Pahl & Beitz design method was used in the design process. The third variant among the three generated variants was chosen and manufactured. The performance test was carried out on a specimen according to ASTM D 638 type 1. It is found that the tensile load was 698 N, and the tensile strength was 16.6 MPa. As a comparison, similar specimens were tested by using UTM tension RTF-2410. The average tensile strength was 17.4 MPa. It can be concluded that the tensile test machine worked adequately with a deviation of 0.8 MPa. This deviation can occur due to differences in specimens.